The Influence of Green Promotion, Brand Image and Environmental Awareness on Purchase Interest - Keprinal, Muhammad; Gunawan , Hamzah (Research Horizon, 2025)
This research aims to analyze the effect of green promotion, brand image and environmental awareness on purchase intention of Le Minerale in Yogyakarta. The independent variables used in this research are green promotion, brand image and environmental awareness, while the dependent variable in this study is purchase intention. This research uses a causal quantitative approach. Data collection was carried out by distributing questionnaires to 100 respondents who had purchased Le Minerale products. The question items of all variables proved to be valid and also reliable. The classic assumption test results in normally distributed data, a regression model that does not occur multicollinearity and does not occur heteroscedasticity. The results of this research indicate that: 1) green promotion has a positive and significant effect on purchase intention; 2) brand image has a positive and significant effect on purchase intention; 3) environmental awareness has no positive and significant effect on purchase intention.